Realities and Perspectives of European Maritime Trade - Bosneagu, Romeo; Coca, Carmen Elena; Sargu, Lilia; Scurtu, Ionut; Corduneanu, Dumitru; Daneci-Patrau, Daniel; Lupu, Sergiu (Acta Universitatis Danubius. Œconomica, 2022)
European maritime trade continues to be primarily driven by the evolution of the European and world economy and business. Although the relationship between economic output and trade in goods appears to be changing, with a marked decline in trade in the total value of Gross Domestic Product in recent years, the demand for maritime transport services remains dependent on the performance of the world economy. While industrial activity, economic production, the number of goods, trade and maritime trade may increase at different rates, these variables remain positively correlated. In the conditions of interdependence and globalization, seaborne trade, with efficiency and profitability, is the engine of economic development and prosperity. The European market for the transport of general goods is determined by the need for such goods worldwide, the world economy, the demographic situation, industrialization, and the surplus and deficit of industrialized goods.